Long term evolution of endothelial function during kidney transplantation. Issue 1 (December 2016) - Kensinger, Clark; Bian, Aihua; Fairchild, Meagan; Chen, Guanhua; Lipworth, Loren; Ikizler, T.; Birdwell, Kelly
Abstract Background Endothelial dysfunction is an important precursor to the development of atherosclerosis, and has been suggested to play a role in the increased cardiovascular risk in patients with end stage renal disease. Endothelial function improves rapidly following post kidney transplantation, but the long term change remains unclear. Hypothesizing that endothelial function would remain improved long term post kidney transplantation, we evaluated the longitudinal change of endothelial function, measured by flow-mediated dilation (FMD) of the brachial artery, from months 1 to 24 post transplantation. Given the previously reported association of fibroblast growth factor 23 (FGF-23) with endothelial dysfunction, we also examined changes in the association between FGF-23 levels and the change in FMD following kidney transplantation. Methods We performed a prospective cohort study of 149 kidney transplant recipients, measuring endothelial function by FMD at months 1, 12, and 24 post-transplant. FGF-23 levels were measured at months 1 and 24 post-transplant. Linear mixed effects models were used to assess both the unadjusted and adjusted outcomes. Results The cohort (mean age 49 ± 13 years) was 74 % male and 75 % white. The median FMD was 6.3 % (IQR: 3.4, 10.2), 5.4 % (IQR: 3.1, 8.5), and 5.6 % (IQR: 3.5, 9.1) at 1, 12, and 24 months, respectively. After adjustment for covariates, compared to month 1, no change occurred in FMD at 12 months (−0.66 %; 95 % CI: −1.81 %, 0.49 %;P = 0.262) or 24 months (−0.25 %; 95%CI: −1.76 %, 1.26 %;P = 0.746). FGF-23 decreased significantly over time (P = 0.024), but there was no significant association between FGF-23 and FMD (P = 0.799). Conclusion Endothelial function remained stable at 12 and 24 months from 1 month post-kidney transplant, indicating that the improved endothelial function seen with transplant is maintained up to 2 years post transplantation. There was also no significant association between FGF-23 and endothelial function following kidney transplantation.